2015
DOI: 10.1158/1078-0432.ccr-14-1358
|View full text |Cite
|
Sign up to set email alerts
|

Novel Actions of Next-Generation Taxanes Benefit Advanced Stages of Prostate Cancer

Abstract: Purpose To improve the outcomes of patients with castrate resistant prostate cancer (CRPC), there is an urgent need for more effective therapies and approaches that individual specific treatments for patients with CRPC. The current studies compared the novel taxane, cabazitaxel with the previous generation docetaxel, and aimed to determine which tumors are most likely to respond. Experimental design Cabazitaxel (CBTX) and docetaxel (DCTX) were compared via in vitro modeling to determine molecular mechanism, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
84
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(88 citation statements)
references
References 42 publications
2
84
1
1
Order By: Relevance
“…Preclinical and clinical experience has documented minimal activity of taxane therapy alone in HSPC (24,25), and transcriptional response to this drug has recently been shown to be largely dependent on hormone status (26), suggesting that specific AR signaling modulates docetaxel insensitivity and that alteration of this signaling might sensitize prostate cancer cells to docetaxel. One well-known feature of AR signaling in prostate cancer involves ERG, which is overexpressed in at least 50% of prostate cancers as a result of gene fusions with genes such as TMPRSS2, SLC45A3, and NDRG1, which have AR promoter regions (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical and clinical experience has documented minimal activity of taxane therapy alone in HSPC (24,25), and transcriptional response to this drug has recently been shown to be largely dependent on hormone status (26), suggesting that specific AR signaling modulates docetaxel insensitivity and that alteration of this signaling might sensitize prostate cancer cells to docetaxel. One well-known feature of AR signaling in prostate cancer involves ERG, which is overexpressed in at least 50% of prostate cancers as a result of gene fusions with genes such as TMPRSS2, SLC45A3, and NDRG1, which have AR promoter regions (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…RB loss has been previously described to be prevalent in, enriched in, and causative for CRPC (34,(36)(37)(38). To expand analyses of the RB pathway to recent clinical findings, alterations in the androgen receptor (AR), RB, cyclin-CDK, and CDK inhibitor profiles were assessed using a cohort of CRPC tissue from the Stand Up to Cancer/Prostate Cancer Foundation (SU2C/PCF) prostate cancer collection ( Figure 1, A and B, and ref.…”
Section: Rb/e2f1 Pathway Disruption Is Frequent In and Preferentiallymentioning
confidence: 99%
“…Androgen ablation therapy is mainly used to treat hormone-sensitive PC. However, in most males usually after 2 to 3 years, metastatic PC leads to an androgen-independent state (7)(8)(9). It is shown that signaling pathways influence cell growth and its inhibition through cell cycle regulation (10).…”
Section: Introductionmentioning
confidence: 99%